The Potential of Cannabidiol for Acute Respiratory Distress Syndrome in COVID-19 - Azimi, Saeid; Saghafi, Fatemeh; Mohammadi, Mohammad H.; Moghimi, Mohammad Hossein; Akhavan, Seyed Ali; Khataminia, Masoud; Shirvani, Maria; Sohrevardi, Seyed Mojtaba; Jamialahmadi, Tannaz; Sahebnasagh, Adeleh; Sahebkar, Amirhossein (Current Pharmaceutical Design, 2023)
COVID-19 disease manifests itself in a wide range of signs and symptoms, beginning with mild symptoms, such as fever, cough, and dyspnea, progressing to acute respiratory distress syndrome (ARDS) and death in some cases. The cytokine storm, or an excess of cytokines released locally, is assumed to be the primary cause of ARDS and mortality in COVID-19 patients. To enhance the survival rate of COVID-19 patients, early management of the cytokine storm with immunomodulators is crucial. Although the effectiveness of some immunosuppressants, such as corticosteroids and tocilizumab, has been studied in clinical trials, the administration of these drugs should be exercised cautiously. Cannabidiol (CBD) is a non-psychotropic phytocannabinoid from Cannabis sativa extracts with anti-inflammatory properties. This review is intended to discuss the possible utility of CBD for the management of COVID-19 patients, particularly those with ARDS.
Keywords: cytokine